Optimization of Production Process of Nano-Calcium Oxide from Pinctada maxima Shell by Using Taguchi Method - Kendri Wahyuningsih; Jumeri Jumeri; Wagiman Wagiman (Universitas Gadjah Mada, 2019)
West Nusa Tenggara is a center of sea oyster farming for Pinctada maxima in Indonesia. The calcium carbonate (CaCO3) compounds in the shell are one of the decomposed natural minerals to produce calcium oxide (CaO) compound which is able to be used as an alternative heterogeneous catalyst in nanometer scale. This research aims to discover the control factors which influence the production process of nanometer-scaled CaO heterogeneous catalyst and choose the best condition in its production process with a better-quality product. Calcined pearl shell (P. maxima) powder is milled by using Shaker mill. The experimental design is performed by using Taguchi method with an orthogonal matrix consisting of 4 control factor variables, i.e. milling time, ball-to-powder weight ratio, the diameter of milling beads and extent of milling the vial. The selection of best control factor variable combination is computed by using multiresponse loss function. ANOVA analysis shows that the product quality parameter of nano-calcium oxide is influenced by all experiment factors. Multi-response loss function analysis results an optimum factor and level combination under process condition happens during the duration of 3 h milling, the ball-to-powder weight ratio is 1:10, the diameter of milling beads is 5 mm and 55% extent of filling the vial.